Analisis Hukum Penyelesaian Sengketa Hak Milik Atas Tanah Menurut Undang-Undang Nomor 5 Tahun 1960 Tentang Peraturan Dasar Pokok-Pokok Agraria - Mustari Efendi; Syaiful Arifin; Diana Ria W. Napitupulu (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
Land has a very important position in human life which can be seen because of the fact, namely it is used as a place to live, a place to be born, a place to earn a living, a place to be buried, and also as a place for ancestors. Therefore, every land must have legal certainty and certainty of rights for its owner, so that there are no disputes over land rights. Efforts towards legal certainty in terms of obtaining land ownership rights are stated in Article 19 of the Basic Agrarian Law Number 5 of 1960 concerning Basic Agrarian Principles which requires the Government to carry out land registration and land certification. The goal is that parties who wish to obtain land ownership rights can easily find out the status and area of ​​the land they wish to own, or that has been owned for certainty of rights in order to avoid land conflicts and disputes. This study uses a descriptive analytical research method that describes facts in the form of secondary data consisting of primary legal basic materials (legislation), secondary legal materials with a normative legal approach, namely a method that uses secondary data sources, namely laws and regulations, legal theories and opinions of scholars, which are then analyzed. Based on the research results, it was found that problems often arise such as negligence by land buyers who control land plots only by holding a Deed of Sale and Purchase as proof of ownership of land rights, without going through the administration of land ownership certificates at the land office. Thus, the legal analysis carried out by the Author in this study is to review the extent of efforts to resolve land ownership.